Estudio de implementación de un Sistema Web para el control y seguimiento de quejas y sugerencias en la Empresa Tía (Sucursal 121) del cantón Ventanas, Provincia Los Ríos - Moreira Tobar, Roberto Carlos (2021)
This case study project emphasizes the analysis of customer service processes, emphasizing the attention to complaints and suggestions made by the customer, with the aim of eliminating all these and proposing an alternative feasible computer solution for thus guaranteeing better service and optimization of resources and improving customer service response times, achieving a competitive advantage over other market competitors. The technique used in this practical case is the quantitative method and the research technique that was carried out was direct observation through the survey tool that will be carried out on users or customers of branch 121 of TIA warehouses since they have the enough experience carrying out the different processes over the years through this It was determined that the control of complaints and suggestions are not carried out adequately because all these processes are carried out manually and not very effective when carrying out the due follow-up and does not help to identify problems or weaknesses of the company The investigation was carried out with this design since it could be transferred to the scene and a data collection instrument (surveys) was applied, aimed at the clientele. This helped to collect necessary data on the process of resolution of complaints presented by citizens and to support the results of the investigation, present the corresponding conclusions and recommendations. After due analysis, we were able to conclude that the TIA warehouse company, being a highly successful multinational company, has the necessary resources to cover the costs for the development of a web system for the control and follow-up of complaints for branch 121 of the VENTANAS canton.